Blending in Internet Communication: Linguistic and Creative Aspect (“VKontakte” Social Network) - L. T. Kasperova; N. V. Smirnova (Научный диалог)
Network blends, occasional neoplasms posted by users of the social network VKontakte under the hashtag #Slovarevo, are studied in a linguo-creative aspect. The main provisions of the theory of blending are formulated as a way of game word formation, which has become widespread in the modern communicative space in general and in the Internet environment in particular. The cognitive foundations of linguo-creativity of blending and the basic principles of conceptual integration that ensure the effective functioning of blends are determined. Structural types of blends are identified, reflecting the main formal methods of constructing contaminants in the network space. The predominance of haplological blends in the illustrative material, inheriting the original words in full and facilitating the decoding of contaminants, has been established. The main mechanisms of the language game based on blending are analyzed, reflecting the high level of metalinguistic reflection of the users of the social network “Vkontakte” involved in punning word formation. Linguistic and creative activity in the Internet environment is characterized in terms of interactivity, interaction between the addresser and the addressee. Cases of communicative failures in the interpretation of blends in the absence of contextual support and the possibility of discursive deployment of their semantics are considered. The implementation of the linguo-creative potential of network blends was assessed based on the triad “forgetive — creative — pseudo-creative”.